Research on digital transformation strategy of China's retail industry based on new retail mode - Yang Xiaoling; Mohd Rahimie Abd Karim; Borhan Sareya Abdullah (Universiti Malaysia Sabah, 2024)
Following decades of rapid expansion, China's retail industry has emerged as a prominent player in global commerce. However, the competition within the retail sector is intensifying. Chinese retail enterprises are now restructuring their business processes with digitalization as the central driving force, upgrading the production, distribution and sales of goods, and deeply integrating online services, offline experiences and modern logistics to establish a new retail model. This paper focuses on analyzing the challenges present in the digital transformation of retail enterprises based on the new retail model and current status of digital transformation in Chinese retail enterprises. It also proposes a strategic model for the digital transformation of these enterprises. Ultimately, this strategy involves establishing a consumer-centric data analysis system, reengineering business processes based on data flow and reorganizing organizational structures while building an intelligent collaborative digital open platform for internal and external resources to achieve successful digital transformation.